1982
DOI: 10.1159/000194501
|View full text |Cite
|
Sign up to set email alerts
|

Fluid Retention and Relative Hypoventilation in Acute Mountain Sickness

Abstract: The presence of pulmonary, cerebral, and/or peripheral edema in acute mountain sickness (AMS) implies a derangement in the body’s handling of water. Previously, we demonstrated water retention and increased symptoms of AMS when hypocapnia was prevented in subjects exposed to simulated high altitude. This led us to the hypothesis that upon ascent to high altitude, those persons who fail to increase their ventilation adequately and hence do not become hypocapnic will retain water reflected as weight gain and wil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
65
2
1

Year Published

1986
1986
2015
2015

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(73 citation statements)
references
References 3 publications
4
65
2
1
Order By: Relevance
“…The latter study suggests, however, that hypoxic depression of ventilation may be associated with AMS. Indeed, direct or indirect measurements of ventilation performed at real or simulated altitude suggest hypoventilation of subjects with AMS compared with controls [5,6,8,10,31]. These observations could be explained by differences in hypoxic depression of ventilation or else by changes of the HVR occurring at high altitude.…”
Section: Discussionmentioning
confidence: 99%
“…The latter study suggests, however, that hypoxic depression of ventilation may be associated with AMS. Indeed, direct or indirect measurements of ventilation performed at real or simulated altitude suggest hypoventilation of subjects with AMS compared with controls [5,6,8,10,31]. These observations could be explained by differences in hypoxic depression of ventilation or else by changes of the HVR occurring at high altitude.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of the respiratory mechanisms contributing to AMS, it has been long recognized that the ventilatory response is reduced in people susceptible to AMS (Hackett et al, 1982). Recently, in a group of people exposed to experimental hypoxia (FIO 2 = 80% SaO 2 ), the acute hypoxic ventilatory response at 5 min (HVR5min) was greater in individuals not susceptible to AMS compared to susceptible individuals (Nespoulet et al, 2012).…”
Section: Sleep Qualitymentioning
confidence: 99%
“…Finally, there are a large number of studies of AMS reported in which both sexes were studied together without differentiating between them (e.g., Hackett et al, 1982;Dean et al, 1990;Anholm et al, 1979;Montgomery et al, 1989). The implicit assumption in the design of these studies was that AMS does not differ between men and women.…”
Section: Introductionmentioning
confidence: 99%